Cognitive effects of dance-movement intervention in a mixed group of seniors are not dependent on hippocampal atrophy - Kropacova, Sylvie; Mitterova, Kristina; Klobusiakova, Patricia; Brabenec, Lubos; Anderkova, Lubomira; Nemcova-Elfmarkova, Nela; Balazova, Zuzana; Rektor, Ivan; Grmela, Roman; Svobodová, Lenka; Vaculikova, Pavlina; Rektorova, Irena (Journal of neural transmission (Vienna, Austria, 2019)
Dance-movement intervention (DMI) offers multi-component stimulation of cognitive functions, and it may ameliorate cognitive deficits in the elderly. We investigated the effects of intensive DMI on the cognitive performances of healthy seniors (HS) and patients with mild cognitive impairment (MCI). In addition, we evaluated whether the baseline MRI hippocampus-to-cortex volume (HV:CTV) ratio (i.e., a marker of a typical AD-specific brain atrophy and of distribution of neurofibrillary tangles in the brain) has any impact on the DMI-induced cognitive changes. The research cohort consisted of 99 subjects who were randomly assigned (in a 1:1 ratio) to a DMI group or to a control (life-as-usual) group. The DMI group consisted of 49 subjects with an average age of 69.16 years (SD = 5.36), of which 34 were HS (69.4%) and 15 had MCI (30.6%). The control group consisted of 50 subjects aged 68.37 years (SD = 6.10), of which 31 were HC (62%) and 19 (38%) had MCI. The DMI group underwent a 6-month intervention, which consisted of 60 lessons supervised by a qualified instructor. Statistical analysis yielded a significant improvement of the figural fluency task as measured by the five-point test in the DMI group as compared to the control group [t (97) = 2.72; p = 0.008]. The baseline HV:CTV ratio was not associated with cognitive changes on that task or with changes in any cognitive domain's Z scores. We observed DMI-induced effect on the test evaluating executive functions across the spectrum of HS and MCI, which was not dependent on the magnitude of AD-related brain pathology.
Keywords: senioři; Mild cognitive impairment; Hippocampus–to-cortex volume ratio; Cognitive Dysfunction; MRI; Aging; exekutivní funkce; Male; Dance-movement intervention; hipokampus; Middle Aged; mužské pohlaví; Executive function; Dance Therapy; atrofie; magnetická rezonanční tomografie; hodnocení výsledků zdravotní péče; Magnetic Resonance Imaging; stárnutí; ženské pohlaví; Humans; Outcome Assessment, Health Care; kognitivní dysfunkce; terapie tancem; lidé středního věku; Executive Function; Female; Aged; lidé; Atrophy; Hippocampus